Numerical investigation of the convective heat transfer coefficient of the human body using a representative cylindrical model - Eferemo, Daniel (Department of Mechanical Engineering, 2018)
The principal objective of this study is to investigate, develop and verify a framework for determining the convective heat transfer co-efficient from a cylindrical model that can easily be adaptable to more complex geometry - more specifically the human body geometry. Analysis of the model under forced convection airflow conditions between the transition velocity of about 1m/s - calculated using the Reynolds number - up until 12m/s were carried out. The boundary condition, however, also included differences in turbulence intensities and cylinder orientation with respect to wind flow (seen as wind direction in some texts). A total of 90 Computational Fluid Dynamic (CFD) calculations from these variations were analysed for the model under forced convective flow. Similar analysis were carried out for the model under natural convection with air flow velocity of 0.1m/s. Here, the temperature difference between the model and its surrounding environments and the cylinder orientation with respect to wind flow were varied to allow for a total of 15 CFD analysis. From these analysis, for forced convection, strong dependence of the convective heat transfer coefficient on air velocity, cylinder orientation and turbulence intensity was confirmed. For natural convection, a dependence on the cylinder orientation and temperature difference between the model and its environment was confirmed. The results from the CFD simulations were then compared with those found in texts from literature. Formulas for the convective heat transfer coefficient for both forced and natural convection considering the respective dependent variables are also proposed. The resulting formulas and the step by step CFD process described in this thesis provides a framework for the computation of the convective heat transfer coefficient of the human body via computer aided simulations. This framework can easily be adaptable to the convective heat transfer coefficient calculations of the human body with some geometric modelling adjustments, thus resulting in similar representative equations for a human geometric model.